Echoes from the Holocaust : philosophical reflections on a dark time - Rosenberg, Alan, 1939-; Myers, Gerald E. (Gerald Eugene), 1923-2009 (Temple Univ. Press, 1988)
This book contains essays that focus on the profound issues and the philosophical significance of the Holocaust.